The fall and rise of inequality - Andreas Schäfer; Klaus Prettner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We investigate the effect of higher education on the evolution of inequality. In so doing we propose a novel overlapping generations model with three social classes: the rich, the middle class, and the poor. We show that there is an initial phase in which no social class invests in higher education of their children, such that the evolution of inequality is entirely driven by the level of bequests. Once a certain income threshold is surpassed, the rich start to invest in higher education of their children, which partially crowds out bequests and thereby reduces inequality in the short run. The better educated children of the rich, however, enjoy higher incomes and inequality starts to rise again. As time goes by, the middle class and eventually also the poor start to invest in higher education, but now the increase in inequality is driven by different levels of education. As the economy proceeds towards a balanced growth path, educational differences between social groups and thus inequality decline again. We argue that (1) the proposed mechanism has the potential to explain the u-shaped evolution of inequality in rich countries in the second half of the 20th century and the first decade of the 21st century and (2) the currently observed increase in inequality is rather a transitory phenomenon.
Keywords: I24; I25; O11; 330